ANALISIS FUNGSI PENILAIAN KINERJA KEPALA SEKOLAH (PPKS) SEBAGAI SUPERVISOR PENDIDIKAN - Susanti; Mieke Yostania; Masrukhan; Ahmad Hariyadi; Su'ad (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2023)
The purpose of this study was to analyze the performance appraisal function of school principals in carrying out one of their roles as educational supervisors in schools. This type of research is descriptive qualitative. Data collection techniques using observation, interviews and documentation studies. Data analysis uses interactive data patterns from Miles & Huberman. Checking the credibility of the data is done by checking the credibility, dependability and confirmability. The results of this study showed that the performance appraisal analysis of school principals is very effective in improving the quality and professionalism of school principals in carrying out their roles. The principal as a supervisor plays an important role in improving teacher professionalism and the quality of education in schools. As a supervisor, the principal is responsible for planning educational programs in schools, progress and development of schools and increasing teacher professionalism through fostering the performance of teachers in schools.